Highly Pathogenic Avian Influenza A(H5N1) Virus: How Far Are We from a New Pandemic? - Giovanni Di Guardo (Veterinary Sciences)
The focus of this commentary is represented by the pandemic risk associated with the highly pathogenic avian influenza (HPAI) A(H5N1) virus, clade 2.3.4.4b. More in detail, the herein dealt pandemic alarm appears to be primarily justified by the huge and progressively growing number of virus-susceptible domestic and wild birds and mammals, including threatened marine mammal species like South American sea lions and elephant seals as well as harbour porpoises, bottlenose dolphins and polar bears. Of major concern is the susceptibility of dairy cattle to HPAI A(H5N1) virus, particularly the documented and unprecedented colonization of host’s mammary gland tissue, resulting in viral shedding through the milk alongside a large series of cases of infection in dairy farm workers in several USA locations. Despite well-documented zoonotic capability, no evidences of a sustained and efficient HPAI A(H5N1) viral transmission between people have been hitherto reported. If this were to happen sooner or later, a new pandemic might consequently arise. Therefore, keeping all this in mind and based upon the lessons taught by the COVID-19 pandemic, a “One Health, One Earth, One Ocean”-centered approach would be absolutely needed in order to deal in the most appropriate way with the HPAI A(H5N1) virus-associated zoonotic and pandemic risk.